2020
DOI: 10.1042/bsr20193995
|View full text |Cite
|
Sign up to set email alerts
|

MiR-489 aggravates H2O2-induced apoptosis of cardiomyocytes via inhibiting IGF1

Abstract: Myocardial infarction (MI) is a major type of cardiovascular disorder worldwide. In this study, we established a new microRNA (miRNA)-mRNA crosstalk network by integrating data obtained from The National Center for Biotechnology Information Gene Expression Omnibus (NCBI GEO). In addition, functional assays, including Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway and Gene Ontology (GO) analyses, were conducted using the Database for Annotation, Visualization, and Integration Discovery (DAVID). In our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…Our study firstly confirmed that IGF1 acted as a target of kurarinone, and kurarinone upregulated IGF1 expression in H 2 O 2 ‐treated KGN cells. Previous studies suggested the protective roles of IGF1 in H 2 O 2 ‐induced cell injury in keratinocytes, hepatocytes, and cardiomyocytes 18–20 . Consistent to these reports, here we found the protective function of IGF1 against oxidative stress in granulosa cells.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study firstly confirmed that IGF1 acted as a target of kurarinone, and kurarinone upregulated IGF1 expression in H 2 O 2 ‐treated KGN cells. Previous studies suggested the protective roles of IGF1 in H 2 O 2 ‐induced cell injury in keratinocytes, hepatocytes, and cardiomyocytes 18–20 . Consistent to these reports, here we found the protective function of IGF1 against oxidative stress in granulosa cells.…”
Section: Discussionsupporting
confidence: 92%
“…Insulin‐like growth factor 1 (IGF1) is one of main regulators involving in follicle development in ovarian, 16 and it regulates ovarian function by repressing granulosa cell apoptosis 17 . Moreover, IGF1 could resist oxidative stress‐induced damage in multiple cell lines, such as keratinocytes, hepatocytes and cardiomyocytes 18–20 . However, whether IFG1 is linked to oxidative stress‐induced granulosa cell injury remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these have been shown as involved in regulation of immune responses, angiogenesis, or wound healing. The three downregulated miRNAs were; miR-137 (angiogenesis and muscle regeneration [ 63 , 64 ]), miR-218 (regulation of cytokines, chemokines and interferon production, hypoxia-responding [ 65 , 66 , 67 ]) and mir-489 (apoptosis and wound healing [ 68 , 69 , 70 ]). Similarly, the three upregulated miRNAs have been reported as involved in regulation of disease relevant responses; miR-730 is an Actinopterygii-specific miRNA responding to bacterial infection in Zebrafish [ 52 , 71 , 72 ]), miR-144 regulates apoptosis/cell cycle control [ 73 ] while the teleost specific miR-2188 responds to viral infection and is likely involved in macrophage differentiation [ 25 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous injection of IGF-1 30 min before left anterior descending artery ligation ameliorated myocardial infarct size and apoptosis [ 159 ]. Downregulation of IGF-1 during I/R through microRNA-320 and microRNA-489 aggravated the extent of myocardial infarction, ventricular remodeling, and apoptotic cell death [ 160 , 161 ], proposing an important IGF-1 mediated endogenous protection against ischemic cell death. This is further affirmed by the findings that genetic depletion of mouse mast cell protease 4—presumably responsible for endogenous IGF-1 degradation—alleviated myocardial infarct size, post-ischemic cardiac dysfunction and remodeling [ 162 ].…”
Section: Modulatory Role Of Myokines On Ros In the Context Of I/rmentioning
confidence: 99%